2019
DOI: 10.1038/s41598-019-46687-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural MRI at 7T reveals amygdala nuclei and hippocampal subfield volumetric association with Major Depressive Disorder symptom severity

Abstract: Subcortical volumetric changes in major depressive disorder (MDD) have been purported to underlie depressive symptomology, however, the evidence to date remains inconsistent. Here, we investigated limbic volumes in MDD, utilizing high-resolution structural images to allow segmentation of the hippocampus and amygdala into their constituent substructures. Twenty-four MDD patients and twenty matched controls underwent structural MRI at 7T field strength. All participants completed the Montgomery-Asberg Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 70 publications
1
42
1
Order By: Relevance
“…The volumes of GC-DG and CA (1-3) were also decreased in unmedicated MDD patients compared with healthy controls [24]. On the other hand, Brown et al [30] reported that there were no significant differences between MDD patients and healthy subjects in hippocampal subfield volume. Recently, we also reported that the volumes of all hippocampal subfields did not significantly differ between MDD patients and healthy controls [31].…”
Section: Discussionmentioning
confidence: 93%
“…The volumes of GC-DG and CA (1-3) were also decreased in unmedicated MDD patients compared with healthy controls [24]. On the other hand, Brown et al [30] reported that there were no significant differences between MDD patients and healthy subjects in hippocampal subfield volume. Recently, we also reported that the volumes of all hippocampal subfields did not significantly differ between MDD patients and healthy controls [31].…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, they may have had structural changes in other hippocampal sub-regions that did not resolve upon remission, consistent with evidence of cumulative hippocampal volume loss in MDD patients in association with total lifetime illness duration ( 15 , 16 ). More specifically, a high-resolution 7T MRI study in patients with MDD revealed hippocampal volume loss in hippocampal sub-regions CA3 and CA1 that correlated with symptom severity ( 41 ). Establishing whether these region-specific volume losses show recovery upon remission requires high resolution longitudinal studies in depressed patients, from acute onset through to remission.…”
Section: Discussionmentioning
confidence: 99%
“…Their weight increased significantly during treatment (S1 Table; S1 Fig); there was no interaction between time (pre vs post) and response (P = .20). The average baseline MADRS score was 31 (SD 5; range [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]; no significant differences arose in baseline MADRS score between responders vs. non-responders (P = .63; not shown). Completers showed a decrease in MADRS score following eight weeks of treatment (Mean, 12; SD, 5; S1 Table).…”
Section: Clinical Responsementioning
confidence: 91%
“…The focus of this work rests on the amygdala and sgACC regions based on extensive prior literature. For example, unmedicated depressed patients have hypermetabolic amygdalae at rest [20]; decreased amygdala volume that correlates with depression severity [27,28]; increased amygdala reactivity to sensory stimuli even without conscious awareness [29,30]; amygdala reactivity prognostic of response to cognitive therapy [31]; sustained amygdala responses to negative words [32]; and disrupted functional connectivity [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%